2022
DOI: 10.22401/anjs.25.3.01
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Organic Matter by Using Titrimetric and Loss on Ignition Methods for Northern Iraqi Governorates Soils

Abstract: The study was carried out to determine soil organic matter content (SOM) using loss on ignition (LOI) and titrant methods. Eighty-four composite soil samples were collected from surface soil of randomly different locations in four governorates of northern parts of Iraq. The percent mean values of SOM recorded were 2.34, 2.399 and 1.821, respectively for Erbil, Sulaymaniyah, Kirkuk, and Duhok soil samples for the LOI method, while lower values were obtained 1.39, 1.595 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Among these, 46% of the SOC d values were two to 26 times greater than SOC w . Similar findings were reported in the studies conducted by Maulood [31], Anand et al [32], and Barwari et al [33], among others, suggesting that LOI-based SOC quantification may result in higher estimates. Previous inquiries indicated that LOI overestimates the carbon content of soils due to the volatilization of hygroscopic and structural water and thermal decomposition of carbonate-containing minerals at temperatures above 375°C [34][35][36].…”
Section: Carbon Content Of Urban Soils Based On Loi and Walkley-black...supporting
confidence: 89%
“…Among these, 46% of the SOC d values were two to 26 times greater than SOC w . Similar findings were reported in the studies conducted by Maulood [31], Anand et al [32], and Barwari et al [33], among others, suggesting that LOI-based SOC quantification may result in higher estimates. Previous inquiries indicated that LOI overestimates the carbon content of soils due to the volatilization of hygroscopic and structural water and thermal decomposition of carbonate-containing minerals at temperatures above 375°C [34][35][36].…”
Section: Carbon Content Of Urban Soils Based On Loi and Walkley-black...supporting
confidence: 89%
“…In the Iraqi Kurdistan region, despite extensive SOM research, there is a noticeable absence of detailed digital SOM maps. While Gravi and Ibrahim [18] employed the ASD Field Spec 3 spectroradiometer for SOM levels in Duhok province, others still rely on time-tested laboratory methods [19,20].…”
Section: Introductionmentioning
confidence: 99%